Religious Tolerance on Social Media: Public Perceptions of Puja Mandala - Ahmad Farid Fanani (Journal of Asian Wisdom and Islamic Behavior, 2026)
Puja Mandala in Nusa Dua, Bali, is a complex of five houses of worship within a single area that offers a unique phenomenon—not only representing interreligious dialogue but also serving as an icon of tolerance. This paper aims to examine how Puja Mandala is interpreted by the public as a symbol of tolerance and how such perceptions are represented through interactions on social media. This study is important to understand the extent to which religious symbols such as Puja Mandala truly function as representations of tolerance rather than merely architectural constructs. Using a mixed-method approach, the analysis was conducted on 2,277 comments from YouTube and TikTok through sentiment analysis combined with library research. The findings show that positive (49.5%) and neutral (50.15%) comments dominate, while negative comments account for only 0.35%, confirming that the public tends to appreciate the diversity embodied in Puja Mandala. The main contribution of this study lies in its effort to bridge the discussion between religious architecture and public perception. This research demonstrates that religious symbols not only function within physical spaces but also disseminate the notion of tolerance on social media, with practical implications for strengthening interfaith harmony in Indonesia.